The Role of Vascular Calcification in Heart Failure and Cognitive Decline - Cheng, Hao-Min (Pulse (Basel), 2018)
Vascular calcification is heterogeneous and triggered by multiple mechanisms. It has been implicated in the development of heart failure with preserved ejection fraction (HFpEF) and cognitive function impairment. Understanding the pathophysiology of vascular calcification may help us improve the management of HFpEF, atherosclerosis, accelerated arterial stiffness, hypertension, and cognitive dysfunction. Currently, there are no effective strategies for treating accelerated arterial stiffness. This may indicate that once arterial stiffness or vascular calcification has developed, it may be less likely to stop the ongoing pathophysiology. Therefore, earlier intervention targeting the probable pathways of vascular calcification may benefit the patients with vascular calcification and related pathological conditions. In this review, we briefly discuss the proposed pathophysiological roles of vascular calcification in the development of heart failure and cognitive decline, the animal models used to study the link between vascular calcification and cardiovascular diseases, and the possible corresponding management strategies.